SAT0245 Improvement in health-related quality of life from anakinra therapy in patients with rheumatoid arthritis not using dmards. (1st June 2001) - Emery, P; Woolley, JM; Chan, WW
Abstract : Background: Objectives: To evaluate the effect of anakinra on health related quality of life (HRQOL) as measured by the Nottingham Health Profile (NHP), in subjects with rheumatoid arthritis not using DMARDs. Methods: In a 24-week, multicenter, randomised, double-blind clinical trial conducted in Europe, 473 subjects received either one of three doses of anakinra (30 mg, 75 mg, or 150 mg) or placebo SC QD. Subjects were excluded if they used DMARDs within six weeks of entry, or if they had failed therapy with more than three DMARDs. The NHP was administered in selected countries at baseline and at weeks 12 and 24 (n = 353). The NHP consists of 38 items which assess physical mobility (MOB), pain (PAIN), energy (ENRG), sleep (SLP), emotional reactions (EMO), and social isolation (ISO). The NHP is scored so that lower scores indicate better HRQOL and negative change scores indicate improvements. The mean change in each NHP scale score was compared between subjects receiving anakinra (all doses combined) and those on placebo. All subjects who completed at least one post-baseline assessment were included (n = 328) and the last-observation was carried forward in the case of missing data. Results: Subjects using anakinra experienced statistically significant improvements in all six NHP scales. These improvements exceeded those for subjects on placebo for all six scales, four of which were statistically significant. Conclusion: Subjects receiving anakinra experienced statistically significant improvements in their NHP scores that exceeded those for subjects on placebo. These improvements were seen in both physical and psychosocial domains. In subjects who are not receiving DMARD therapy, anakinra leads to improvements in health-related quality of life.